A Brief Report on Fetishism in Romania: An Approach Based on Gender and Sexual Orientation. Issue 1 (2nd January 2022) - Berariu, Florin Gabriel; Jitaru, Mihaela; Candel, Octav Sorin
Abstract: Objectives: With this research, we aimed to assess the level of fetishism in Romania, to explore the gender and sexual orientation differences and to inspect its relationship with sexual satisfaction and well-being. Methods: This study analyses data from 525 participants from the non-clinical population. Results: The analyses showed that some levels of fetishism are present in almost 70 % of the sample, that queer participants report higher scores and that it does not impact sexual satisfaction and well-being. Conclusion: These findings can be used for a better understanding of fetishism and its impact by both clinicians and individuals with fetishes.